2020
DOI: 10.18203/issn.2455-4529.intjresdermatol20203749
|View full text |Cite
|
Sign up to set email alerts
|

A study on safety and efficacy of intralesional vitamin D3 in cutaneous warts

Abstract: <p class="abstract"><strong><span lang="EN-US">Background: </span></strong><span lang="EN-US">Immunotherapy is an upcoming treatment modality for cutaneous warts. Majority of the treatment modalities used for warts are destructive and can be painful, causes scarring and are not suitable for multiple warts. Immunotherapy overcome these shortcomings and it has shown good response both in injected and distant warts. Literature shows only very limited data on the use of immunoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…There are very few studies on the treatment of difficult-to-heal palmoplantar warts with Bleomycin. [ 15 16 17 18 19 20 ] Table 3 compares the outcome of our study to those of others in the treatment of difficult-to-heal palmoplantar warts with IL Bleomycin. Complete clearance was reported in 95.5% of patients, which was similar to Shumer et al ’s finding of 94% after only two sessions of treatment, others reported 73–92%, which could be due to a lower number of sessions or a longer time between sessions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There are very few studies on the treatment of difficult-to-heal palmoplantar warts with Bleomycin. [ 15 16 17 18 19 20 ] Table 3 compares the outcome of our study to those of others in the treatment of difficult-to-heal palmoplantar warts with IL Bleomycin. Complete clearance was reported in 95.5% of patients, which was similar to Shumer et al ’s finding of 94% after only two sessions of treatment, others reported 73–92%, which could be due to a lower number of sessions or a longer time between sessions.…”
Section: Discussionmentioning
confidence: 97%
“…Swelling at the injection site lasting more than a week was seen in 8.2%, compared to 86% in the study by Aziz et al . [ 20 ] No systemic toxicity or Raynaud’s phenomenon was observed during study and follow-up period. [ 16 ] Recurrence was not seen in our study but recurrence was high in Aziz et al which may be because of a smaller number of sessions.…”
Section: Discussionmentioning
confidence: 99%
“…11 Close to our study, a therapeutic response of Intralesional injections of vitamin D3 with complete resolution was found by Akula et al 12 Potlapati et al found complete resolution of plantar warts in (76.6%), no response in 3.4% of cases. 13 Intralesional vitamin D3 is an effective treatment modality in treating plantar warts. Differences in complete clearance rates are attributed to host immunity and strain of HPV.…”
Section: Discussionmentioning
confidence: 99%
“…Common warts are the commonest type of benign epidermal proliferation of the skin caused by human papillomavirus, transmitted mainly by direct skin-to-skin contact [1,2] . Despite warts usually, having self-limiting and spontaneous resolution taking place within months to years, there are chances of spreading to other sites and other persons; so local destruction using, electrocoagulation, cryotherapy, laser therapy, or topical keratolytic is a commonly employed treatment modality performed [3,4] .…”
Section: Introductionmentioning
confidence: 99%